Peran Lembaga Keuangan Desa dalam Meningkatkan Kesejahteraan Masyarakat - Mardiana, Andi; Pakaya, Wining E (Institut Agama Islam Negeri Kendari, 2017)
The research looked at the role of Rural Financial Institutions in improving public welfare of Oleleh Village of Kabila Bone in Bone Bolango District. This institution is an extension of the local government of Bolango Bone, this is the program for the welfare of society with the help of venture capital, either as fishermen, farmers as well as a small merchant, the results of this study found that the role of the village financial institutions can contribute to improve the welfare of society . This can be measured by several indicators, those are the return of agricultural land controlled by the middlemen, the primary requirement before the establishment of “LKD?” sometimes difficult to be fulfilled, but after this institution was established and worked, it can increase the income and the living conditions of local society